Function and specificity of synthetic Hox transcription factors in vivo. - Papadopoulos, D.K.; Vukojevic, V.; Adachi, Y.; Terenius, L.; Rigler, R.; Gehring, W.J. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Homeotic (Hox) genes encode transcription factors that confer segmental identity along the anteroposterior axis of the embryo. However the molecular mechanisms underlying Hox-mediated transcription and the differential requirements for specificity in the regulation of the vast number of Hox-target genes remain ill-defined. Here we show that synthetic Sex combs reduced (Scr) genes that encode the Scr C terminus containing the homedomain (HD) and YPWM motif (Scr-HD) are functional in vivo. Synthetic Scr-HD peptides can induce ectopic salivary glands in the embryo and homeotic transformations in the adult fly, act as transcriptional activators and repressors during development, and participate in protein-protein interactions. Their transformation capacity was found to be enhanced over their full-length counterpart and mutations known to transform the full-length protein into constitutively active or inactive variants behaved accordingly in the synthetic peptides. Our results show that synthetic Scr-HD genes are sufficient for homeotic function in Drosophila and suggest that the N terminus of Scr has a role in transcriptional potency, rather than specificity. We also demonstrate that synthetic peptides behave largely in a predictable way, by exhibiting Scr-specific phenotypes throughout development, which makes them an important tool for synthetic biology.